The Effectiveness of a Packaged Intervention Including Point-of-View Video Modeling in Teaching Social Initiation Skills to Children With Autism Spectrum Disorders. (September 2019) - Kouo, Jennifer Lee
Deficits in social communication and interaction have been identified as distinguishing impairments for individuals with an autism spectrum disorder (ASD). As a pivotal skill, the successful development of social communication and interaction in individuals with ASD is a lifelong objective. Point-of-view video modeling (VM) has the potential to address these deficits. By presenting only what a person might see from his or her viewpoint, it may be more effective than other forms of VM, in limiting irrelevant stimuli and providing a clear frame of reference to facilitate imitation. The current study investigated the use of point-of-view VM in teaching social initiations (e.g., greetings). Using a multiple baseline across participants design, five kindergarten participants were taught greetings using a packaged intervention, which included point-of-view VM, video priming, verbal praise, reinforcement, and prompting. Immediately before and after viewing the entire point-of-view video model, the participants were evaluated on their greetings with a trained, typically developing peer serving as a communication partner. Specifically, the greetings involved participants' abilities to shift their attention toward the peer who entered the room, maintain attention toward the peer, and engage in an appropriate greeting (e.g., hi, hello). Both generalization and maintenance were tested. Overall, the data suggest point-of-view VM is a promising intervention for increasing greetings. However, both generalization and maintenance were limited. Despite the limitations of the study and variable results, there are a number of implications moving forward for both practitioners and future researchers examining point-of-view modeling.